Analisis Kualitas Sistem SLIMS Terhadap Kepuasan Mahasiswa Dengan Metode E-Servqual dan Importance Performance Analysis - Pangestu, M Yoga; Saputra, Eki; Angraini, Angraini; Hamzah, Muhammad Luthfi (Jurnal Inovtek Polbeng Seri Informatika, 2024)
SLIMS at the XYZ University library has been built since 2014 and began to be implemented in 2018 and has been running until now. During implementation there were several problems, including incomplete book collections, this caused students to prefer choosing books manually. Apart from that, sometimes there are still some problems that occur when processing the data used. Many users still don't understand how to use SLIMS. This research aims to measure the level of user satisfaction and provide suggestions for improving the SLIMS system. The method used in this research is E-Servqual which has 5 variables in this method and the Importance Performance Analysis method is used to compare user assessments of the level of importance of service quality. The data obtained from this research was distributing questionnaires to a sample of 100 respondents. Data processing was carried out using the SMART-PLS 4 tool. The analysis results obtained for the level of user satisfaction were 3 variables that were significant and influenced user satisfaction, namely the Empathy, Responsiveness and Tangible variables. Meanwhile, the other 2 variables, namely Assurance and Reliability, do not have a significant relationship with user satisfaction. This shows that students are still quite satisfied and a science analysis was carried out on 4 quadrants to evaluate service factor based on the level of user satisfaction